Контурная система для определения магнитных моментов технических объектов - Крамчанин, Евгений Геннадиевич (НТУ "ХПИ", 2010)
Рассмотрены принципы работы контурных динамических систем с угловым перемещением технических объектов для определения магнитных моментов. Предложена функциональная схема системы c угловым перемещением технического объекта. Рассмотрены практические аспекты реализации такой системы.

The operation principles of contour dynamic systems for measuring of magnetic moments in technical objects with an angular displacement are considered. A functional diagram of the system is proposed. Practical aspects of implementing such systems are considered.
Contour system for measuring of magnetic moments in technical objects
Keywords: функциональная схема; измерительный контур; угловое перемещение; магнитная сигнатура объекта; power equipment; magnetic moment; measurement; dynamic system; signature